Unintended Consequences of Interview Faking: Impact on Perceived Fit and Affective Outcomes - Charbonneau, Brooke D. (2021)
Drawing on signalling theory, we propose that use of deceptive impression management (IM) in the employment interview could produce false signals, and individuals hired based on such signals may incur consequences once they are on the job—such as poor perceived fit. We surveyed job applicants who recently interviewed and received a job to investigate the relationship between use of deceptive IM in the interview and subsequent perceived personjob and person-organization fit, stress, well-being, and employee engagement. In a twophase study, 206 job applicants self-reported their use of deceptive IM in their interviews at Time 1, and their perceived person–job and person–organization fit, job stress, affective well-being, and employee engagement at Time 2. Deceptive IM had a negative relationship with perceived person–job and person–organization fit. As well, perceived fit accounted for the relationship between deceptive IM and well-being, employee engagement, and job stress. The findings indicate that using deceptive IM in the interview may come at a cost to employees